2023
DOI: 10.1093/mnras/stad206
|View full text |Cite
|
Sign up to set email alerts
|

The imprint of bursty star formation on alpha-element abundance patterns in Milky Way-like galaxies

Abstract: Milky Way-mass galaxies in the FIRE-2 simulations demonstrate two main modes of star formation. At high redshifts star formation occurs in a series of short and intense bursts, while at low redshifts star formation proceeds at a steady rate with a transition from one mode to another at times ranging from 3 to 7 Gyr ago for different galaxies. We analyse how the mode of star formation affects iron and alpha-element abundance. We find that the early bursty regime imprints a measurable pattern in stellar elementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Far-ultraviolet and Hα emissions can be used to quantify the burstiness of observed galaxies (Sparre et al 2017). Recently, Flores Velázquez et al (2021 and Parul et al (2023) used star formation indicators to measure the burstiness of galaxies from the FIRE project simulations. They found that Milky Way-mass galaxies have highly bursty star formation at early times and time-steady SFR at later times.…”
Section: Dark Matter Core Formationmentioning
confidence: 99%
“…Far-ultraviolet and Hα emissions can be used to quantify the burstiness of observed galaxies (Sparre et al 2017). Recently, Flores Velázquez et al (2021 and Parul et al (2023) used star formation indicators to measure the burstiness of galaxies from the FIRE project simulations. They found that Milky Way-mass galaxies have highly bursty star formation at early times and time-steady SFR at later times.…”
Section: Dark Matter Core Formationmentioning
confidence: 99%